The films of Lenny Abrahamson a filmmaking of philosophy - Monahan, Barry 1973- (Bloomsbury Academic, 2018)
"A thorough reflection on the stylistic and philosophically-profound cinematic work of Ireland's most exciting contemporary directors, Lenny Abrahamson"...
Includes bibliographical references and filmography
Keywords: Abrahamson, Lenny -- Criticism and interpretation; Abrahamson, Lenny -- 1966-; Motion picture producers and directors -- Ireland; Film